ANALISIS TEORI TAM TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA MAKASSAR UTARA - Masdar, Nisma Ariskha (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
This study focuses on two main variables in TAM, namely Perceived Usefulness and Perceived Ease of Use, and how both contribute to the level of taxpayer compliance. This study uses a quantitative approach with a survey method by distributing questionnaires to individual taxpayers registered at the North Makassar Tax Office. The data obtained were analyzed using multiple linear regression to test the effect of independent variables on the dependent variable. The results of the study indicate that Perceived Usefulness and Perceived Ease of Use have a positive and significant effect on taxpayer compliance. This finding indicates that increasing understanding and ease of access to e-Filling can encourage taxpayer compliance in fulfilling their tax obligations.